PREVAILING AMERICAN DEMOCRACY WITHIN AFRICAN-AMERICAN LITERATURE OF AMANDA GORMAN’S THE HILL WE CLIMB: STUART HALL’S AUDIENCE RECEPTION ANALYSIS - Alifiadita Nindyarini Wirawan; Achmad Munjid (Rubikon : Journal of Transnational American Studies, 2022)
The appealing part of a literary work is to enable the audience to feel emotionally connected with a literary work, leading them to produce diverse interpretations. In this respect, the occurrence of Amanda Gorman’s poem of The Hill We Climb is capable of attracting American citizens’ attention to deliver their perception of the work. The intensity of American society’s reactions can be seen in how the audience expresses their responses on YouTube. Therefore, the writer decided to analyze the phenomenon further by applying Stuart Hall’s reception theory aimed to prevail on how American society perceives the poem. Finally, the result of the analysis shows that the majority of Americans perceived the work as encouragement in refining the principles of American democracy, which were categorized as dominant readings. On the other hand, several audiences who interpreted the poem as a form of hope are included as negotiated readings that deliver different opinions but align with the poet’s perception. The last is oppositional readings that interpret the poem as a redundant work, shown by the audience’s incapability to comprehend the poem comprehensively. Briefly, the variety of the audience’s interpretations is because of diverse perceptions possessed by the audience in perceiving the message of democracy within the poem, which is influenced by their backgrounds.